2016
DOI: 10.1016/j.tjog.2016.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in a noncommunicating rudimentary horn of a unicornuate uterus: Prerupture diagnosis and management

Abstract: Diagnosis and management of rudimentary horn pregnancy remain a challenge. We should be alert to prenatal ultrasound with the intention of making an earlier diagnosis, thereby resulting in decreased maternal morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 9 publications
0
41
0
Order By: Relevance
“…Pregnancy in a non-communicating rudimentary horn is believed to develop from transperitoneal sperm migration. This is a rare condition but may result in life-threating complications such as rupture, intra-abdominal bleeding and hemorrhagic shock [17]. In the present study, 2 patients (14.3%) presented to our clinic in a shock state.…”
Section: Discussionmentioning
confidence: 54%
“…Pregnancy in a non-communicating rudimentary horn is believed to develop from transperitoneal sperm migration. This is a rare condition but may result in life-threating complications such as rupture, intra-abdominal bleeding and hemorrhagic shock [17]. In the present study, 2 patients (14.3%) presented to our clinic in a shock state.…”
Section: Discussionmentioning
confidence: 54%
“…As a result very few (10%) of these pregnancies reach full term out of which only 2% of the fetuses can survive [10]. Although antenatal diagnosis of pregnancy in rudimentary horn is still tricky, advanced first trimester scanning may provide a clue for early diagnosis [4,9]. But only few cases of rudimentary horn pregnancy were diagnosed in early trimester prior to rupture so far [8,11].…”
Section: Discussionmentioning
confidence: 99%
“…us a high index of suspicion is needed as in the majority of cases it is detected a er it gets ruptured [3,6]. Ectopic pregnancy in the rudimentary horn of unicornuate uterus is associated with life threatening complications, one of which is uterine rupture with a 50% risk [4,5]. Here, I report a case of ectopic pregnancy in the rudimentary horn of a unicornuate uterus at gestational age of 16 weeks.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…While studies have reported rudimentary horn pregnancies, as well as tubal and cornual ectopic pregnancies occurring in both communicating and non-communicating horns,7 there is little published literature about ectopic pregnancies in the undescended ovary or tube in patients with an isolated unicornuate uterus. These ectopic pregnancies are associated with severe maternal morbidity and even mortality 8.…”
Section: Discussionmentioning
confidence: 99%